Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Di Marketplace Shopee: Studi Pada Masyarakat Kecamatan Alam Barajo Kota Jambi - Suci Salira Ayatusifa; Mohammad Orinaldi; Agusriandi Agusriandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the current era of globalization, many trading activities are carried out with the help of technology. With the emergence of internet echnology, people's lives have become easier, one of which is online shopping. The practical advantage of online shopping is that with the help of internet technology it can be done anywhere, anytime and without limits. Thus, online shopping applications can always see the products available there. Product quality, price and promotion are one of several factors that influence consumer considerations in purchasing decisions. Quality products at affordable prices and lots of promotions will attract people's interest. The purpose of this research is to find out and analyze The effect of product quality, price and promotions on purchasing decisions in the shopee marketplace. The research method used is descriptive quantitative. The samples taken were 100 respondents Using proportionate stratified random sampling technique. This study used the SPSS calculator version 22. The results showed that product quality, price and promotion had a positive and significant effect on purchasing decisions at the Shopee marketplace. Based on data analysis in this study, these variables are valid and reliable. In testing the classical assumptions of this study, the distribution is normal, there is no heteroscedasticity and multicollinearity.